Effects of Melatonin on Hepatic and Aortic Tissue STAT-3 Levels in Hypercholesteraemic Rats - Sezgin, Dilsad; Sahna, Kezban; Aslan, Gulnur; Sahna, Engin (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY